Analisis kemampuan pemecahan masalah matematika ditinjau dari self-efficacy matematis siswa kelas VIII - Alan Abdulah; Majid Majid; Franky Alfrits Oroh (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
This study originated from empirical observations showing that junior high school learners demonstrated limited capacity in resolving mathematical tasks, especially those related to the Pythagorean Theorem, a condition assumed to have a strong association with the degree of students’ mathematical self efficacy. This investigation applied a descriptive qualitative design that emphasized an in depth case study framework. The participants involved six learners from class VIII A at SMP Negeri 1 Tomilito who were intentionally chosen using purposive criteria from an overall population of 23 students. The information required for the study was obtained by administering a self efficacy questionnaire, conducting a mathematical problem resolution assessment, and carrying out structured interviews. The results revealed that learners possessing high self efficacy demonstrated systematic problem resolution and fulfilled all indicators proposed by Polya. Learners with moderate self efficacy showed weaknesses in planning and precision, whereas those with low self efficacy experienced obstacles in comprehending problems and were unable to finalize solutions. Overall, the findings confirm that mathematical self efficacy affects students’ levels of mathematical problem resolution ability.